Determinants of the Quality of hotel Services in Lowersilesian Hotels and Methods for Developing Quality - Jaremen, Daria Elżbieta (Turyzm/Tourism, 2001)
For contemporary hotels quality is becoming one of the most important factors strengthening their position on the highly competitive market and leading to economic success. The author attempts to define the internal and external determinants of the development of the hotel industry, as well as the factors which increase and decrease the quality of service in Lower Silesian hotels. She also presents a study of the quality of service in these hotels and discusses the methods applied.